The islamic management practices among consultants in MAA Takaful Kota Bharu / Mohamad Arif Aizat Ariffin - Ariffin, Mohamad Arif Aizat (2015)
This research are attempts to analyse the Islamic management practices among consultants in MAA Takaful Kota Bharu by examine the five variables which are planning, organising, leading, motivation and controlling. Islamic management practices are important because it will show how that the respondents will act to the organizational commitment. By taking the MAA Takaful Kota Bharu’s employees as a target, the data gathered through questionnaire and was analysed using SPSS software. From the analysis, it can be conclude that the result shows that all independent variables except the organizing and controlling had a significant and high positive relationship with the dependent variable which is employees’ organizational commitment. As stated, the independent variables organising and controlling have a negative relationship towards the dependent variable